Complication Rates After TRUS Guided Transrectal Systematic and MRI-Targeted Prostate Biopsies in a High-Risk Region for Antibiotic Resistances - Wenzel, Mike; Theissen, Lena; Preisser, Felix; Lauer, Benedikt; Wittler, Clarissa; Humke, Clara; Bodelle, Boris; Ilievski, Valentina; Kempf, Volkhard A. J.; Kluth, Luis A.; Chun, Felix K. H.; Mandel, Philipp; et al. (Frontiers in Surgery, 2020)
Introduction: There is still an ongoing debate whether a transrectal ultrasound (TRUS) approach for prostate biopsies is associated with higher (infectious) complications rates compared to transperineal biopsies. This is especially of great interests in settings with elevated frequencies of multidrug resistant organisms (MDRO). Material and Methods: Between 01/2018-05/2019 230 patients underwent a TRUS-guided prostate biopsy at the department of Urology at University Hospital Frankfurt. Patients were followed up within the clinical routine that was not conducted earlier than six weeks after the biopsy. Among 230 biopsies, 180 patients took part in the follow-up. No patients were excluded. Patients were analysed retrospectively regarding complications, infections and underlying infectious agents or needed interventions. Results: Of all patients with follow up, 84 patients underwent a systematic biopsy (SB) and 96 a targeted biopsy (TB) after MRI of the prostate with additional SB. 74.8% of the patients were biopsy-naïve. The most frequent objective complications (classified by Clavien-Dindo) lasting longer than one day after biopsy were hematuria (17.9%, n=32), hematospermia (13.9% n=25), rectal bleeding (2.8%, n=5) and pain (2.2%, n=4). Besides a known high MDRO prevalence in the Rhine-Main region, only one patient (0.6%) developed fever after biopsy. One patient each (0.6%) consulted a physician due to urinary retention, rectal bleeding or gross hematuria. There were no significant differences in complications seen between SB and SB + TB patients. The rate of patients who consulted a physician was significantly higher for patients with one or more prior biopsies compared to biopsy-naïve patients. Conclusion: Complications after transrectal prostate biopsies are rare and often self-limiting. Infections were seen in less than 1% of all patients, regardless of an elevated local prevalence of MDROs. Severe complications (Clavien-Dindo ≥IIIa) were only seen in 3 (1.7%) of the patients. Repeated biopsy is associated with higher complication rates in general.